A modified‐live porcine reproductive and respiratory syndrome virus (PRRSV)‐1 vaccine protects late‐term pregnancy gilts against heterologous PRRSV‐1 but not PRRSV‐2 challenge. Issue 5 (13th March 2018) - Jeong, J.; Kang, I.; Kim, S.; Park, S.‐J.; Park, K. H.; Oh, T.; Yang, S.; Chae, C.
Summary: The objective of this study was to determine the efficacy of a commercially available porcine reproductive and respiratory syndrome virus (PRRSV)‐1 modified‐live virus (MLV) vaccine against PRRSV‐1 and PRRSV‐2 challenge in late‐term pregnancy gilts. Gilts were vaccinated with the PRRSV‐1 MLV vaccine at 4 weeks prior to breeding and then challenged intranasally with PRRSV‐1 or PRRSV‐2 at 93 days of gestation. After PRRSV‐1 challenge, vaccinated pregnant gilts had a significantly longer gestation period, significantly higher numbers of live‐born and weaned piglets and a significantly lower number of stillborn piglets at birth compared to unvaccinated pregnant gilts. No significant improvement in reproductive performance was observed between vaccinated and unvaccinated pregnant gilts following PRRSV‐2 challenge. Vaccinated pregnant gilts also exhibited a significantly improved reproductive performance after challenge with PRRSV‐1 compared to vaccinated pregnant gilts following PRRSV‐2 challenge. The PRRSV‐1 MLV vaccine was able to reduce PRRSV‐1 but not PRRSV‐2 viremia in pregnant gilts. Vaccinated gilts also showed a significantly higher number of PRRSV‐1‐specific IFN‐γ‐secreting cells (IFN‐γ‐SC) compared to PRRSV‐2‐specific IFN‐γ‐SC. The data presented here suggest that the vaccination of pregnant gilts with a PRRSV‐1 MLV vaccine provides good protection against PRRSV‐1 but only limited protection against PRRSV‐2 challenge in late‐term pregnancy gilts based on improvement of reproductive performance, reduction in viremia and induction of IFN‐γ‐SC.